Altruism through the prism of philosophy and religion (Journal of Philosophy Culture and Political Science, 2018)
Nobody can ever doubt that altruism is a watchword of the modern ethics. Yet, the question about how one can have people living in accordance with the principle of altruism remains unanswered. If we betake ourselves to analyze the very evolution of the «altruism» notion, the roots of which go deeply into the traditional religious practice of mercy and compassion, it will become quite clear that it is the religious sentiment that can play very notable a role as far as living up to altruistic ideals is concerned. The article also tells about the connotation and practice of the «altruism» notion in the modern world as well as stands up for the necessity and importance of altruistic attitude toward man and the universe. By the way of analysis of the Western and Earstern thinkers, important parallels are drawn between the religious and secular ways of thinking, making it evident that altruism can and should be cultivated not only by people of the secular mindset, but those who are deeply religious, too.Key words: altruism, «Ego», imperative, «Sufism», Qur’an, the Enlightenment Age.